Argumenty religijne w sferze publicznej. Uwagi o postulacie prywatyzacji religii - Sztajer, Sławomir (Polskie Towarzystwo Religioznawcze, 2012)
Sławomir Sztajer – RELIGIOUS ARGUMENTS THE PUBLIC SPHERE. REMARKS ON THE DEMAND FOR PRIVATIZATION OF RELIGION This article discusses the issue of the place of religion in the public sphere with special reference to the situation in Europe. It differentiates between normative and descriptive understanding of privatization and focuses on the liberal demand for privatization of religion. A minimal version of this demand is relatively widespread in European liberal democracies. This is a demand that in the public debate religious reasons should be translated into secular reasons, i.e. reasons that do not depend on theological considerations or religious authorities. After presenting selected conceptions of privatization of religion and arguments that support them, I quote several counter-arguments and argue that the demand for privatization cannot constitute an indisputable basis for liberal democracies.